Przestrzeń szkolna i jej znaczenie dla mieszkańców Okręgu Szkolnego Lwowskiego w latach 1918–1939 - Walasek, Stefania (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2021)
The notion of “space” can be used in relation to schools, i.e., the school buildings and their environment. On this basis we focus our interest on the location of classrooms and their environment which ought to allow children to relax and to play. Throughout the interwar period school buildings would constitute the focus of the attention of numerous social circles. In the opinion of an outstanding Polish pedagogue, Marian Falski, the school building was crucial to the future of schooling and national culture. From the perspective of pedagogy a newly constructed school building would create or supplement the school network, facilitating the fulfilment of the children’s school duty. Analysis of the numerous documents describing the actions aimed to construct new school buildings within the Lwów School District allows one to notice the increasing interest of the local communities in the issue. The members of the local community would actively participate in the construction initiatives. It was noticed that this was the way to develop education on the level of public schools. The creation of a centre of cultural and educational life of the local community within the new school was of no lesser importance.
Keywords: school space; school building; school duty; school hygiene